COMMERCIALIZATION OF STUDENT IDEAS IN THE DEVELOPMENT OF HIGHER EDUCATION AND INCREASING BUSINESS INCUBATOR ACTIVITY - Narzullaev Shodiyor (American Journals, 2024)
This article provides information on the advantages of providing financial independence to educational institutions of the Republic of Uzbekistan, including ways to commercialize innovative business ideas of students, models of financial support for scientific and technological development projects and programs. Also, the opinions of foreign and local scientists regarding the financing of the business incubator system are presented.
Keywords: Modelling, small business, startup, innovation, idea, development, entrepreneurship, office work, information, training, consulting, legal, service, incubation, financing.